Bioremediation, bioenergy and stress biology, issue 2014 - Singh, D. P.; Singh, M. P. (Cellular and Molecular Biology, 2014)
Environmental problems are now perceived to be a complex issue. There is paradigm shift in the goods and services offered by the ecosystem which directly affect the very survival of human being on this planet. There is urgent need for deep understanding of the nature and natural ecosystems. The deteriorating quality of environment as a whole has jeopardized the life and made the planet unsafe for all living creatures. Effective management of current environmental issues and problems is not in place despite the manifold advancement in the field of science and technology. Sometimes, a proper understanding of the nature of environmental problem is also lacking. In view of these, a three day International Conference on "Environmental Technology & Sustainable Development : Challenges and Remedies” was successfully organized by the Department of Environmental Science at Babasaheb Bhimrao Ambedkar University, Lucknow (India) during February 21-23, 2014.